The American Past and Present: A New Historicist Approach to The Adventures of Tom Sawyer - Montenegro Bonilla, Joe (2018)
To clarify the relationship between a literary work and its socio-historical context, this article explores Mark Twain’s The Adventures of Tom Sawyer, from a New Historicist perspective. The voices perceived throughout the text (those of the author, the characters, the reader, and the historical and social settings) combine to discuss the reality of American culture in the 19th century and in the present. Thus, this study provides the necessary space to put New Historicism into practice, seeking a more comprehensive approach to the interpretive possibilities of Twain’s work